2007
DOI: 10.1177/0193841x06289044
|View full text |Cite
|
Sign up to set email alerts
|

Challenging the Courtesy Bias Interpretation of Favorable Clients’ Perceptions of Family Planning Delivery

Abstract: Favorable client perceptions of provider's interpersonal behavior in contraceptive delivery, documented in clinic exit questionnaires, appear to contradict results from qualitative evaluations and are attributed to clients' courtesy bias. In this study, trained simulated clients requested services from Ministry of Health providers in three countries. Providers excelled in courteousness/respect in Peru and Rwanda; in India, providers were less courteous and respectful when the simulated clients chose the pill. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 18 publications
0
19
0
1
Order By: Relevance
“…It is possible that the relatively high levels of satisfaction reported in our study were caused by desirability bias; several other studies have shown that clients are reluctant to express negative opinions of services when interviewed at health facilities [62,63]. By adding open-ended questions to the interview and by conducting additional key informant interviews in communities, we were able to triangulate the findings and overcome this limitation.…”
Section: Discussionmentioning
confidence: 90%
“…It is possible that the relatively high levels of satisfaction reported in our study were caused by desirability bias; several other studies have shown that clients are reluctant to express negative opinions of services when interviewed at health facilities [62,63]. By adding open-ended questions to the interview and by conducting additional key informant interviews in communities, we were able to triangulate the findings and overcome this limitation.…”
Section: Discussionmentioning
confidence: 90%
“…Beginning in the mid-1980s, a number of simulated client studies have been employed to assess family planning service quality within the regions of Latin America and the Caribbean, sub-Saharan Africa, and South Asia (Hardee et al, 2001, Huntington et al, 1990, Leon et al, 2007, Leon et al, 1994, Maynard-Tucker, 1994, Naik et al, 2010, Population Council, 1992, Schuler et al, 1985). Findings from these studies frequently highlight deficiencies in service quality, utilizing the Bruce framework to identify areas of investigation, and on occasion have been used to measure the impact of recent provider trainings (Huntington et al, 1990, Population Council, 1992, Naik et al, 2010) or assess the quality of services for a specific facility type (Hardee et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…One approach for collecting data on service quality while avoiding many of the biases inherent with tools from the situation analysis is use of the simulated client method (Hardee et al, 2001, Huntington and Schuler, 1993, Leon et al, 2007, Madden et al, 1997, Maynard-Tucker, 1994, Naik et al, 2010, Population Council, 1992, Schuler et al, 1985). In this approach, a woman pretending to be an actual new family planning client presents at a health facility and undergoes a family planning counseling session.…”
Section: The Simulated Client Methodsmentioning
confidence: 99%
“…For example, self-regulation has been associated with all the constructs in this model (Chasnoff et al, 1998; Doan, Fuller-Rowell, & Evans, 2012; Novak & Clayton, 2001; Olson et al, 1997; Riggs, Kobayakawa Sakuma, & Pentz, 2007; Wiebe et al, 2009) – it is plausible that the prenatal environment and maternal health impacts adolescent girls’ self-regulation, resulting in adolescents that are poorly regulated and display more internalizing and externalizing symptoms as well as engaging in smoking and behaviors that increase adiposity. Research that examines the role of adolescent self-regulation in moderating relations between maternal prenatal health and internalizing and externalizing symptoms may help to elucidate those effects and provide further insight into the processes underlying these findings.…”
Section: Discussionmentioning
confidence: 98%